Xanthagaricus montgomeryensis sp. nov. (Agaricaceae, Agaricales) from Chichawatni Forest, Punjab Pakistan - Fatima, Nadia; Abdul Nasir Khalid (Phytotaxa, 2023)
A new species of Xanthagaricus, is described based on collections made from Chichawatni Forest, District Sahiwal, Punjab, Pakistan. It is characterized by medium-sized basidiomata, pale-yellowish pileus with yellowish to dark brown squamules, and small oblong to ellipsoid yellowish basidiospores (3.99–4.87 × 2.12–2.85 µm). Molecular phylogenetic analyses based on the Internal Transcribed Spacers (ITS1-5.8S-ITS2 = ITS) and D1/D2 domains of the large subunit (28S) of the nuclear ribosomal DNA, also support the finding that Xanthagaricus montgomeryensis is distinct from other known species within the genus Xanthagaricus.